Urine-based point-of-care testing for factor-Xa-inhibitors in acute ischemic stroke patients: a feasibility study - Doeppner, Thorsten R.; Olbricht, Linus; Maxhuni, Toska; Alhaj Omar, Omar; Sachs, Ulrich J.; Juenemann, Martin B.; Huttner, Hagen B.; Gerner, Stefan T. (Frontiers in Neurology, 2023)
Introduction: Direct oral anticoagulants(DOACs) have become widely used in clinical practice for preventing thromboembolic events. Point-of-care testing methods, particularly those based on urine samples, offer a promising approach for rapid and accurate assessment of DOAC presence. This pilot study aims to evaluate the utility of a urine-based DOAC dipstick test as a point-of-care tool for identifying DOAC presence in acute ischemic stroke(AIS) or transient ischemic attack(TIA) patients. Patients and methods: This prospective pilot study included patients with AIS/TIA eligible for DOAC-measurement. After exclusion of 3patients, 23patients with DOAC-intake(DOAC group; factor-Xa-inhibitors;n=23) and 21patients without DOAC-intake (control-group) remained for analyses. The urine-based DOAC dipstick test and parallel blood-based specific DOAC-level assessment were performed in all patients. Time-intervals of sampling urine/blood sampling and result of DOAC-test were recorded to analyze a potential time benefit based on dipstick evaluation.Results: The urine-based DOAC dipstick test demonstrated high sensitivity(100%) and specificity(100%), correctly identifying all patients with anticoagulatory activity due to DOAC intake (i.e. anti-Xalevel≥30ng/ml). Moreover, the visual readout of the test provided semiquantitative information on drug-specific anti-Xa levels, showing a sensitivity of 83% and specificity of 93% to detect anti-Xa levels ≥120ng/ml. The dipstick test exhibited a median time-benefit of 2:25hours compared to standard blood-based DOAC-level testing.Discussion: The results of this pilot study underline the efficacy of urine-based point-of-care testing as a rapid and reliable method for assessing DOAC presence in patients with acute ischemic stroke.The value of this tool for clinical decision-making in future stroke management needs to be established in future trials.